Study on the mechanism of MDSC-platelets and their role in the breast cancer microenvironment - Han, Xinpu; Song, Xiaotong; Xiao, Zhigang; Zhu, Guanghui; Gao, Ruike; Ni, Baoyi; Li, Jie (Frontiers in Cell and Developmental Biology, 2024)
Myeloid-derived suppressor cells (MDSCs) are key immunosuppressive cells in the tumor microenvironment (TME) that play critical roles in promoting tumor growth and metastasis. Tumor-associated platelets (TAPs) help cancer cells evade the immune system and promote metastasis. In this paper, we describe the interaction between MDSCs and TAPs, including their generation, secretion, activation, and recruitment, as well as the effects of MDSCs and platelets on the generation and changes in the immune, metabolic, and angiogenic breast cancer (BC) microenvironments. In addition, we summarize preclinical and clinical studies, traditional Chinese medicine (TCM) therapeutic approaches, and new technologies related to targeting and preventing MDSCs from interacting with TAPs to modulate the BC TME, discuss the potential mechanisms, and provide perspectives for future development. The therapeutic strategies discussed in this review may have implications in promoting the normalization of the BC TME, reducing primary tumor growth and distant lung metastasis, and improving the efficiency of anti-tumor therapy, thereby improving the overall survival (OS) and progression-free survival (PFS) of patients. However, despite the significant advances in understanding these mechanisms and therapeutic strategies, the complexity and heterogeneity of MDSCs and side effects of antiplatelet agents remain challenging. This requires further investigation in future prospective cohort studies.